The deras: Culture, diversity and politics - Singh, Santosh K.; Juergensmeyer, Mark (Haryana (India) Penguin Random House, 2025)
More than a decade ago, intrigued by his encounter with a few people and a chance discussion about their religious beliefs, Santosh K. Singh began delving deeper into the phenomenon of the dera. What followed thereafter was an extensive engagement with this belief system.